2020
DOI: 10.1016/j.jad.2019.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Association of antepartum depression, generalized anxiety, and posttraumatic stress disorder with infant birth weight and gestational age at delivery

Abstract: Background: Low-and middle-income countries bear a disproportionate burden of preterm birth (PTB) and low infant birth weight (LBW) complications where affective and anxiety disorders are more common in the antepartum period than in industrialized countries.Objective: To evaluate the extent to which early pregnancy antepartum depression, generalized anxiety disorder, and posttraumatic stress disorder (PTSD) are associated with infant birth weight and gestational age at delivery among a cohort of pregnant women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 66 publications
1
26
0
2
Order By: Relevance
“…Furthermore, different from other studies in China (44,45), the association between antepartum depression and birth weight and birth weight z-scores in our study was not significant. Studies in other countries also suggested no evidence that antepartum depressive symptoms are associated with birth weight (15) or a higher odds of delivering a low-birth-weight infant (16), which was consistent with our conclusion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, different from other studies in China (44,45), the association between antepartum depression and birth weight and birth weight z-scores in our study was not significant. Studies in other countries also suggested no evidence that antepartum depressive symptoms are associated with birth weight (15) or a higher odds of delivering a low-birth-weight infant (16), which was consistent with our conclusion.…”
Section: Discussionsupporting
confidence: 92%
“…In summary, according to existing studies, there is no general conclusion regarding the relationship between maternal depression and neonatal outcomes, (15,16,34) and this issue deserves further investigation. Because of the lack of attention in China, neither issue has been sufficiently studied.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the study, we found that prenatal maternal stress not only increased plasma corticosterone, but also decreased the weight gain of offspring. It has also been discovered that the presence of generalized anxiety disorder during pregnancy increases the incidence of low birth weight infants ( Gelaye et al, 2020 ). Further, using multiple behavioral experiments, the results showed that prenatal maternal stress leaded to the decline of independent and inquiry behavior ability in new and different environment of open-field test, decreased responsiveness to rewards in sucrose preference test and the generation of despair in suspended tail test of offspring, betoken that the prenatally stressed offspring had emergence of emotional behavior damage.…”
Section: Discussionmentioning
confidence: 99%
“…The 2019/2020 Australian bushfire crisis is known to have elicited stress among pregnant women with asthma (Asthma Australia, personal communication), and previous studies have associated prenatal stress with low birth weight and preterm birth [ 39 ], including a study linking in utero stress related to a natural disaster (Montreal Ice storm) with lowered birth weights [ 40 ]. Furthermore, low birth weight and preterm birth are known risk factors for asthma and respiratory illnesses in childhood.…”
Section: Introductionmentioning
confidence: 99%